Implementasi Nilai-nilai Islami pada Proses Rekrutmen Karyawan - Sri Budi Cantika Yuli; Novi Primita Sari (Universitas Islam Raden Rahmat, 2021)
This study aimed at determining the implementation of Islamic values in the recruitment process (Case Study at University of Muhammadiyah Malang-UMM). This research applied qualitative method through a phenomenological approach. The informants of this study were (1) University Leaders; (2) Employees. Further, the data collected were analyzed using qualitative data analysis techniques, namely: Data Reduction, Data Presentation, and Conclusion Drawing. The results of this study indicated that the recruitment process at UMM: 1) in accordance with Islamic values sourced from the Qur'an and Hadith; 2) UMM leaders have accomplished the mandate that was showed in selecting employees and establishing the law fairly according to Q.S. An Nisa [4]: 58 and Q.S. Al Maidah [5]: 8. UMM Leaders appoint the most worthy and appropriate employees as in Q.S. An Nisaa [4]: 59; 4) UMM leaders choose employees of the highest quality selectively in accordance with the words of the Prophet Muhammad in HR. Baihaqi; 5) UMM Leaders choose capable and trustworthy employees according to Q.S. Al Anfaal [8]: 27.